A survey of recent empirical tests of the purchasing power parity hypothesis - GIOVANNETTI, G. (PSL Quarterly Review, 2013)
The work reviews the empirical literature on Purchasing Power Parity (PPP) in the period of floating exchange rates, 1973-1990, with special attention to the studies addressing the issue of the long run validity of the hypothesis. The different versions of PPP are described and several theoretical reasons put forward to explain deviations from it are outlined. Some empirical problems common in different studies are also analysed. The results of a number of recent empirical studies are then surveyed in terms of both methodology and findings. JEL: E21, E40, F31